Agus Moh Najib's Thoughts on the Interconnection of Islamic Law and National Law - Muhajir Muhajir; Ihda Shofiyatun Nisa'; Akhmad Munawar; Suud Sarim Karimullah (IAIN Manado, 2023)
The number of controversies and debates about integrating Islamic law into the national legal system in Indonesia has led to many counter-productive perceptions, so progressive thinking is needed all parties can accept that. Therefore, this study examines the thoughts of Agus Moh Najib, a Muslim scholar, on integrating Islamic law into the national legal system to create a fair legal system by the demands of society and the state. Methodologically, this research uses a philosophical approach with library research and is also descriptive-analytical qualitative research. The results of this study state that Islamic Law and Indonesian law have several interrelationships and interconnections perspectives on Agus Moh Najib's. He provides recommendations that to maximise the interconnectivity of Islamic law to national law, the first step that needs to be taken is to redesign, reformulate and renovate the ushul fiqh building, which is the basis for the formation of Islamic law without having to tear it down by reviewing existing concepts and theories so that the role of ushul fiqh can be more optimal in developing Islamic legal science that contributes to the formation of laws and regulations in Indonesia. Then harmonisation is carried out between Islamic law and various legal sciences developed in Indonesia regarding subject matter and language. In other words, it is necessary to strive for the formation of the Islamic law that is in harmony with legal science in general based on the ideal moral norms of the core teachings of Islam and also considers the culture and empirical realities that exist in plural Indonesian society.